Characterization of a novel modification of a CHO-produced mAb: Evidence for the presence of tyrosine sulfation. Issue 6 (18th August 2017) - Zhao, Jia; Saunders, Jason; Schussler, Svetlana Dukleska; Rios, Sandra; Insaidoo, Francis Kobina; Fridman, Aleksandr L.; Li, Huijuan; Liu, Yan-Hui
ABSTRACT: Herein we describe the investigation of a Chinese hamster ovary (CHO)-expressed human mAb molecule found partially modified by a +80 Da adduct. This mass difference, suggestive of a single sulfation or phosphorylation addition, was observed by mass analysis of the intact and reduced molecule by mass spectrometry (MS). The modification was located on tyrosine 31 (Y31) of the light chain in the complementarity-determining region 1 by liquid chromatography (LC)-MS peptide mapping and electron transfer dissociation fragmentation. The complete loss of the 80 Da modification moiety during collision induced dissociation fragmentation suggested this modification could not be a tyrosine phosphorylation. Treatment of the mAb with alkaline phosphatase confirmed our hypothesis. Western blot experiment using anti-tyrosine sulfation antibody and LC retention time correlation with corresponding synthetic sulfated peptides further confirmed the identification of tyrosine sulfation on the light chain. The unique sequence motif with neighboring acidic amino acids and local secondary structure might play a role to make Y31 a substrate residue for sulfation. This type of modification, to our knowledge, has not been previously reported for CHO-produced human IgG antibodies.